Benign Intracerebral Hemorrhage: A Population at Low Risk for Hematoma Growth and Poor Outcome. Issue 8 (16th April 2019) - Li, Qi; Yang, Wen‐Song; Shen, Yi‐Qing; Xie, Xiong‐Fei; Li, Rui; Deng, Lan; Yang, Ting‐Ting; Lv, Fa‐Jin; Lv, Fu‐Rong; Wu, Guo‐Feng; Tang, Zhou‐Ping; Goldstein, Joshua N.; et al.
Abstract : Background: To define benign intracerebral hemorrhage (ICH) and to investigate the association between benign ICH, hematoma expansion, and functional outcome. Methods and Results: We analyzed a prospectively collected cohort of patients with ICH, who presented within 6 hours of symptom onset between July 2011 and February 2017 to a tertiary teaching hospital. Follow‐up computed tomographic scanning was performed within 36 hours after initial computed tomographic scanning. Benign ICH was operationally defined as homogeneous and regularly shaped small ICH. The presence of benign ICH was judged by 2 independent reviewers (Q.L., W.Y.) on the basis of the admission computed tomographic scan. Functional independence was defined as a modified Rankin Scale score of 0 to 2 at 3 months. The associations between benign ICH, hematoma expansion, and functional outcome were assessed by using multivariable logistic regression analyses. A total of 288 patients with ICH were included. Benign ICH was found in 48 patients (16.7%). None of the patients with benign ICH had early hematoma expansion. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of benign ICH for predicting functional independence at 3 months were 30.7%, 96.6%, 90.0%, 60.0%, and 0.637, respectively. Conclusions: Patients with benign ICH are at low risk of hematoma expansion and poor outcome. These patients may be safe for less intensive monitoring and are unlikely to benefit from therapies aimed at preventing ICH expansion.